Dynamic Simulation of Bulk Polymerisation of Styrene Using ODE Solver Within Matlab Software - Eugene Hien Yoong, Ng (2013)
The title of this study was to investigate the dynamic simulation of bulk polymerisation of styrene using ODE solver within MATLAB software. The objectives of this study were to develop the a simulation research on bulk polymerisation of styrene using 2,2’ azobisisobutyronitrile catalyst (AIBN) catalyst in batch reactor by using ODE solver within MATLAB software and to determine the initial amount of initiator and batch time to yield desired values of monomer conversion (m) and the number average molecular weight (Xn) at fixed temperature 373K. The results later on were compared with those obtained by Wan Ibrahim (2011) using CVP technique within gPROMS software and also the results obtained by Ekpo (2006). The model equations were developed and adapted similar to those used by Wan Ibrahim (2011) and Ekpo (2006). The model equations were posed as initial value ODE problems and solved using ODE15s solver within MATLAB software. The trend of results showed that the batch time for lower monomer conversion (m) was lower compared to the batch time for higher monomer conversion (m) for each number average molecular weight (Xn). The initial amount of initiator achieved in this study was lower compared to that obtained by Ekpo (2006) but the batch time achieved in this study varied with that obtained by Ekpo (2006). Comparing with the results obtained by Wan Ibrahim (2011), initial initiator concentration needed in this study was lower than that needed in Wan Ibrahim (2011)’s study, but the batch time achieved in this study was much higher compared to that obtained by Wan Ibrahim (2011). As a conclusion, the use of ODE solver within MATLAB software in simulating the dynamic problem of bulk polymerisation of styrene was successful. The initial amount of initiator and batch time was able to be determined and the results achieved were able to compete with the results obtained by Wan Ibrahim (2011) and Ekpo (2006). However, it was recommended that the future study could be done by considering the chain transfer effect and optimal temperature in the study using the same method and software.